ANAESTHESIOLOGY AS A FUTURE SPECIALTY - Mahmood, Khalid; Shamim, Asad; Khan, Muhammad Umair; Alam, Tasneem; Khalid, Usman; Jaffery, Asad Ullah (Pakistan Armed Forces Medical Journal, 2021)
Objective: To ascertain the various aspects directing the undergraduates at Quetta Institute of medical sciences towards anesthesiology as future profession/specialization. Study Design: Cross sectional study. Place and Duration of Study: Quetta Institute of Medical Sciences, Quetta Pakistan, from Mar to Apr 2019. Methodology: Study was conducted among final year medical students with the help of a printed questionnaire consisting of 15 Multiple Choice Questions. The questionnaire provided the required database to explore various factors that influence undergraduates to select their future specialization based on demography and specialty preferences. Results: A total of 65 undergraduates completed the response sheet. While 45 (68.8%) participants were females and 20 (31.2%) were males, 62 (95.4%) were single (unmarried or divorced) and had no children 63 (96.9%). Medicine proved to be the most favourate specialty with 20 (31.4%) student opting for it whereas anesthesiology was chosen by 4 (6.1%) students. Conclusion: Anesthesiology still remains a less popular choice among the medical students of Pakistan particularly Quetta Institute of Medical Sciences due to multifaceted factors. Inferior prestige of the specialty was the most significant factor in deciding against anaesthesiology.